Bougie-assisted endotracheal intubation in the pragmatic airway resuscitation trial. (January 2021) - Bonnette, Austin J.; Aufderheide, Tom P.; Jarvis, Jeffrey L.; Lesnick, Jason A.; Nichol, Graham; Carlson, Jestin N.; Hansen, Matthew; Stephens, Shannon W.; Colella, M. Riccardo; Wang, Henry E.
Abstract: Objective: Paramedics may perform endotracheal intubation (ETI) while treating patients with out-of-hospital cardiac arrest (OHCA). The gum elastic Bougie (Bougie) is an intubation adjunct that may optimize intubation success. There are few reports of Bougie-assisted intubation in OHCA nor its association with outcomes. We compared intubation success rates and OHCA outcomes between Bougie-assisted and non-Bougie ETI in the out-of-hospital Pragmatic Airway Resuscitation Trial (PART). Methods: This was a secondary analysis of patients receiving ETI enrolled in the Pragmatic Airway Resuscitation Trial (PART), a multicenter clinical trial comparing intubation-first vs. laryngeal tube-first strategies of airway management in adult OHCA. The primary exposure was use of Bougie for ETI-assistance. The primary endpoint was first-pass ETI success. Secondary endpoints included overall ETI success, time to successful ETI, return of spontaneous circulation, 72-h survival, hospital survival and hospital survival with favorable neurologic status (Modified Rankin Score ≤3). We analyzed the data using Generalized Estimating Equations and Cox Regression, adjusting for known confounders. Results: Of the 3004 patients enrolled in PART, 1227 received ETI, including 440 (35.9%) Bougie-assisted and 787 (64.1%) non-Bougie ETIs. First-pass ETI success did not differ between Bougie-assisted and non-Bougie ETI (53.1% vs. 42.8%; adjusted OR 1.12, 95% CI: 0.97–1.39). ETI overall success was slightly higher in the Bougie-assisted group (56.2% vs. 49.1%; adjusted OR 1.19, 95% CI: 1.01–1.32). Time to endotracheal tube placement or abandonment was longer for Bougie-assisted than non-Bougie ETI (median 13 vs. 11 min; adjusted HR 0.63, 95% CI: 0.45–0.90). While survival to hospital discharge was lower for Bougie-assisted than non-Bougie ETI (3.6% vs. 7.5%; adjusted OR 0.94, 95% CI: 0.92–0.96), there were no differences in ROSC, 72-h survival or hospital survival or hospital survival with favorable neurologic status. Conclusion: While exhibiting slightly higher ETI overall success rates, Bougie-assisted ETI entailed longer airway placement times and potentially lower survival. The role of the Bougie assistance in ETI of OHCA remains unclear.